A rare case of transient coma after epidural analgesia during labour - Naved, Saad Ahmed; Amjad, Zakaria; Parpia, Sadiq Shoukat Ali (Journal of the Pakistan Medical Association, 2026)
Epidural analgesia is a widely used method for pain relief during labour, but it carries a risk of rare and serious complications. This case report presents a 28-year-old primigravida who developed a transient coma following the administration of a bolus dose of 1% lidocaine for epidural analgesia. Within 15 minutes of administration, the patient became unresponsive, with a significant drop in oxygen saturation. After prompt resuscitation, the patient underwent a caesarean section under general anaesthesia. The case highlights the rare but potentially life-threatening complications associated with epidural analgesia, including high spinal blocks and sensory deafferentation. Timely recognition and intervention are essential for managing these complications and ensuring maternal and foetal safety. This case emphasises the importance of careful monitoring, appropriate dosing, and preparedness in epidural anaesthesia practice. Keywords: Epidural analgesia, transient coma, high spinal block, sensory deafferentation, labour analgesia.